Cartilage tympanoplasty for retraction pocket of the tympanic membrane in children - Urík, Milan; Sobotková, Kateřina; Bartoš, Michal; Machač, Josef; Kruntorád, Vít; Jarkovský, Jiří (Frontiers in Pediatrics, 2024)
Background: Retraction pocket (RP) of the tympanic membrane (TM) is a common pathology in children that can cause ossicular chain erosion, cholesteatoma formation, and potentially life-threatening complications of cholesteatoma. This study assessed the functional and anatomical results of cartilage grafting in children with severe RP of the TM. Methods: This was a retrospective review of 212 children from a tertiary referral center. Results: We identified significant differences in hearing results, indication criteria, and location of TM fixation between stages II and III of RP (according to Charachon). We observed a significantly higher incidence of RP in boys than in girls. Conclusions: Cartilage tympanoplasty for retraction pocket of the tympanic membrane in children is a safe procedure with good anatomical and hearing results